Features of health changes and its subjective adoption by teen in specialized and professional education - Merkulova, Tetiana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Aim. Determining the characteristics of subjective perception of health, depending on its existing disorders in adolescents studying in various types of educational institutions. Materials and methods. The study of the state of health according to the results of in-depth medical examinations and subjective perception of health by adolescents according to the results of a screening survey of 273 senior students (10–11 grades), who studied in two gymnasiums of Kharkiv, and 320 students of three vocational education institutions in Kharkiv. Results. High pathological prevalence rates were found among high school students (2672.4 ‰) compared with students in vocational schools (2026.5 ‰). The girls’ health, regardless of the form of training, was distinguished by more negative characteristics. An analysis of the subjective perception of existing problems with adolescents’ own health showed a higher «level of ill health» among vocational school students (19.7 ± 0.4) points versus (17.6 ± 0.3) points among high school students. The structure of schoolchildren’s complaints is dominated by asthenic manifestations (40.0 ± 0.8), the phenomena of hypovitaminosis (25.3 ± 0.5), cardiac rheumatological disorders (21.4 ± 0.6), while among students of vocational schools more often endocrine system disorders (24.6 ± 0.4) and neuropsychiatric disorders (24.5 ± 0.5) points. Conclusions. The opposite of the situation in the complaints of adolescents and the data of medical examinations testifies to the low quality and lack of proper monitoring of in-depth medical examinations among adolescents who have begun vocational training. Negative trends in the health status of adolescents with various forms of education have been identified, which indicates the need to strengthen preventive work in order to prevent the negative impact of harmful factors in a modern educational institution.